Zero-dynamics attacks on networked control systems. (September 2021) - Pasha, Syed Ahmed; Ayub, Ayesha
Abstract: The coupling of physical systems with information technologies infrastructure in a networked control system (NCS) has a number of advantages such as remote control, reduced system complexity, low maintenance cost and improved system efficiency. But these benefits come at the cost of making the NCS vulnerable to cyberphysical attacks on the communication layer. One such class of attacks is the zero-dynamics attack (ZDA) which targets the internal dynamics of an NCS with the potential to cause serious damage to the physical system while remaining stealthy. A better understanding of how ZDAs are constructed will enable more effective countermeasures. In this paper, we discuss two approaches for constructing a ZDA and demonstrate using three industrial processes studied in this context perhaps for the first time. Highlights: Networked control systems are vulnerable to attacks on the communication layer. Zero-dynamics attacks remain stealthy, targeting the internal dynamics of a system. Geometric control and fault detection based methods generate similar attack vectors. Zero-dynamics attacks rapidly destabilize industrial plants causing physical damage.